SIPANDUK Digital Public Service Innovation: An E-Service Quality Approach - Mala Malantiawati; Sri Wulandari (Sahabat Publikasi, 2026)
The SIPANDUK (Population Administration Service Information System) application is a digital service innovation developed by the Kuningan Regency Population and Civil Registration Office to make it easier for the public to process population documents online. The objective of this study is to assess the service quality of the SIPANDUK application, identify the obstacles hindering its implementation, and examine the efforts made to improve the quality of SIPANDUK services. This study employed a descriptive qualitative approach, utilizing data sources such as observations, interviews, and documentation from key informants and supporting informants. The theory used is E-Service Quality by Parasuraman, Zeithaml, and Malhotra (2005), which consists of seven dimensions (efficiency, system availability, fulfillment, privacy, responsiveness, compensation, and contact). The results of the study indicate that the SIPANDUK application is not yet optimal in the dimensions of efficiency, fulfillment, and compensation. The suboptimal efficiency is caused by the low level of public awareness regarding the application. In the fulfillment dimension, technical challenges remain, specifically regarding the limited features for user account recovery. Additionally, the lack of an official compensation mechanism has prevented the handling of user complaints from operating at full capacity. Meanwhile, the SIPANDUK application has achieved optimal performance in the dimensions of system availability, privacy, responsiveness, and contact. Efforts to improve service quality are being undertaken through increased public awareness of the application, the development of account recovery features, and the establishment of a clearer and more structured compensation mechanism.